2021
DOI: 10.1097/qai.0000000000002556
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Weight Gain Following ART Initiation in ART-Naïve People Living With HIV in the Current Treatment Era

Abstract: Objectives: Evaluate differences in weight change by regimen among people living with HIV (PLWH) initiating antiretroviral therapy (ART) in the current era. Methods: Between 2012 and 2019, 3232 ART-naïve PLWH initiated ≥3-drug ART regimens in 8 Centers for AIDS Research Network of Integrated Clinical Systems sites. We estimated weight change by regimen for 11 regimens in the immediate (first 6 months) and extended (all follow-up on initial regimen) peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 38 publications
3
64
1
Order By: Relevance
“…Our data extend findings from prior studies demonstrating greater weight gain associated with INSTI-based regimens as observed in several cohort studies and RCTs including ADVANCE [ 4 , 6 ], NAMSAL [ 13 ], and other studies [ 3 , 5 , 7 , 14–16 ]. Our analysis has one of the largest sample sizes to date and includes a multinational population.…”
Section: Discussionsupporting
confidence: 90%
“…Our data extend findings from prior studies demonstrating greater weight gain associated with INSTI-based regimens as observed in several cohort studies and RCTs including ADVANCE [ 4 , 6 ], NAMSAL [ 13 ], and other studies [ 3 , 5 , 7 , 14–16 ]. Our analysis has one of the largest sample sizes to date and includes a multinational population.…”
Section: Discussionsupporting
confidence: 90%
“…Data demonstrating INSTI-associated excess weight gain have most consistently implicated DTG and BIC; fewer studies have demonstrated an association with raltegravir (RAL) or elvitegravir/cobicistat (EVG/c) [ 55–64 ]. Several analyses have found that individuals born female have greater likelihood of INSTI-associated weight gain than individuals born male [ 16 , 56 , 61 ].…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%
“…It has been argued that the exaggerated weight gain identified when comparing INSTIs with other classes may stem from viral kinetics and faster viral load reduction with INSTIs, leading to faster or more pronounced return-to-health changes. However, several studies that analyzed differences in weight over time after initiation of INSTIs vs other agents found differential weight gain at time points when the viral suppression rates were equivalent, so this seems unlikely to be the explanation [ 55 , 62 ].…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%
“…The newer formulation, tenofovir alafenamide (TAF), does not cause renal dysfunction but is associated with weight gain, an unwanted side effect in those with normal or elevated weight prior to starting therapy. Indeed, weight gain appears to be amplified with TAF in combination with second-generation integrase strand transfer inhibitors (INSTIs) such as dolutegravir or bictegravir [ 47 , 48 , 49 , 50 ]. Unlike some other antiretroviral drug classes, NRTIs are not specifically linked with diarrhea or other GI symptoms [ 51 ].…”
Section: Antiretroviral Adverse Effects In People Living With Hiv (Pl...mentioning
confidence: 99%
“…Dolutegravir and bictegravir are also both available in coformulations with NRTIs as single-tablet regimens for HIV treatment. While weight gain can occur after the initiation of any antiretroviral regimen and is at least in part associated with the “return to health” phenomenon, there is a clearly delineated association between the initiation of INSTI-based regimens—particularly dolutegravir and bictegravir—and weight gain compared with PI and NNRTI regimens [ 47 , 48 , 49 , 72 , 73 , 74 , 75 ]. Enhanced weight gain is a particular challenge in a population where diabetes, cardiovascular disease and other metabolic conditions are more prevalent than in the general population [ 72 ].…”
Section: Antiretroviral Adverse Effects In People Living With Hiv (Pl...mentioning
confidence: 99%